Acute Arginine Supplementation Is Associated with Increased Growth Hormone in Younger Healthy Males: A Randomized Controlled Trial. (29th May 2020) - Apolzan, John; Rood, Jennifer; Beyl, Robbie; Yang, Shengping; Greenway, Frank; Lieberman, Harris
Abstract: Objectives: Assess the effects of the amino acid arginine on growth hormone (GH), other metabolites, and mood. Arginine is reported to increase GH, but the mechanism is not known. It was hypothesized prolactin mediated this effect since it is similar in structure to GH and, like GH, is secreted by the pituitary gland. Methods: Thirty physically active healthy young males (18–39 y; 18.5–25 kg/m 2 ) were enrolled in a randomized, double-blind, placebo-controlled, crossover trial. Two days prior and 1 day following each treatment a standardized diet was provided that maintained arginine at 3–5 g/d. Arginine or placebo treatments in the form of a beverage were consumed after an overnight fast. Treatment conditions were separated by at least a one week washout period. The beverages contained either 10 g of arginine or 0 g (placebo). Blood was collected at baseline and 1.5, 3.0, and 24 hr post treatment. Plasma GH, prolactin, amino acids, glucose, insulin, triacylglycerols, thyroid hormones, sex hormone binding globulin (SHBG), testosterone, cortisol, and dehydroepiandrosterone (DHEA) were assessed. The Profile of Mood States (POMS) was administered at the same time as blood draws. Repeated measures ANOVAs were used to estimate treatment effects at each time point. Results: Arginine increased plasma arginine at 1.5, 3.0, and 24 hr ( P  ≤ 0.001) and GH at 24 hr ( P ˂ 0.05) but not other time points. Arginine increased glucose and insulin at the 1.5 and 3.0 hr ( P ˂ 0.05) but not 24 hr. Arginine did not affect any other dependent measure ( P > 0.05) including prolactin. When only individuals with detectable levels of GH (responders; n  = 16) were analyzed separately, arginine increased GH at the 1.5 ( P ˂ 0.05) but not the 3.0 or 24 hr time points. Among the responders, arginine also increased thyroid stimulating hormone (TSH) at the 24 hr time point ( P ˂ 0.05) but not the 1.5 and 3.0 hr time points. Conclusions: Arginine supplementation modestly increased growth hormone. Despite their similar structures, prolactin secretion was not elevated following arginine supplementation, thus another mechanism is responsible for growth hormone secretion. Funding Sources: DoD and NIH P30DK072476. Views expressed are those of the authors and do not reflect official policy of the Army, DoD, or US Government.